Pengabdian kepada Masyarakat Edukasi Membangun Lingkungan Positif, Menjaga Anak dari Pergaulan Buruk pada Panti Asuhan Pintu Elok Pamulang - Ussholikhah, Diah Anisa; Rafli, Muhamad; Rohyana, Sigit; Marni; Irenne Putren, S.Pd., M.Pd. (Abdimisi, 2025)
This community service (PKM) is motivated by the children's vulnerability in the orphanage to negative associations, requiring structured intervention to build character defense. The partner problem is the need for a specific, applied prevention program at Pintu Elok Orphanage against negative behaviors. The main objective is to equip children with an in-depth understanding of the characteristics, impact, and refusal methods for bullying, school truancy, and playing until they lose track of time. The method combined detailed educational counseling with Role-Playing simulations and interactive games ("Kindness Balloon" & "True or False") to reinforce refusal skills. The results demonstrated a clear increase in awareness among the children, particularly in identifying bullying (physical and verbal) and the dangers of undisciplined behavior. This success is marked by the strengthening of the collective commitment within the orphanage to maintain a safe and positive environment against harmful influences. Keywords: Negative Behaviors; Anti-Bullying; Self-Discipline; Orphanage; Positive Environment